Music in childhood from preschool through the elementary grades - Campbell, Patricia Shehan; Scott-Kassner, Carol; Kassner, Kirk (Australia Schirmer Cengage Learning, 2014)
As inspirational as it is informative, this text combines the best research and practical knowledge to give music education students the necessary tools to take to their future classroom. This comprehensive text presents contemporary theories and practices of music education including strategies for developing pitch, vocal, rhythmic, instrumental, listening, movement and creative responses in children. It includes chapters on multiculturalism, motivation and management, special learners, assessment, and curriculum integration and development.
The multiple meanings of music for children -- From theory to practice in teaching music to children -- Methods of teaching music to children -- The singing child -- Pitch and the child -- The moving child -- Rhythm and the child -- The playing child -- The listening child -- The creating child -- Motivation and management -- Curriculum design -- Assessment and evaluation -- Music in an integrated curriculum -- Music, children, and cultural diversity -- Music for exceptional children.
Spiral bound.
Includes bibliographical references (pages 439-447) and index.
Keywords: Music -- Instruction and study; School music -- Instruction and study; Preschool music -- Instruction and study